Alopecia Areata: Pathogenesis, current treatments, and future perspectives - Wojciechowska, Karolina; Brzozowska, Monika; Wardal, Wiktoria; Furlepa, Natalia; Rzenno , Robert; Matuszewska, Marcelina; Wicha, Katarzyna; Sidz, Natalia; Tomaszewska, Magdalena; Jedlikowska, Wiktoria (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Alopecia areata (AA) is a chronic autoimmune disorder characterized by non-scarring hair loss, often presenting as round patches. The disease is thought to result from an immune dysregulation. Current research suggests that the loss of immune privilege in hair follicles plays a key role, leading to their destruction by autoreactive T-cells. This review, based on scientific articles retrieved from PubMed and Google Scholar, aims to examine available treatment options and summarize the current state of understanding alopecia areata pathogenesis. State of knowledge: The treatment approach depends on disease severity. The severity of the disease is graded according to the SALT scale. For limited hair loss, topical therapies such as glucocorticosteroids, minoxidil, anthralin, diphenylcyclopropenone (DPCP), and phototherapy are commonly employed. In severe cases, systemic therapies like oral corticosteroids, methotrexate, and other immunosuppressants are used. Recent advancements highlight Janus kinase (JAK) inhibitors as promising therapies, with clinical trials showing their effectiveness in refractory AA cases. Additionally, emerging treatments like stem cell-based therapies are under investigation, offering hope for the future. Conclusions: Despite progress in therapeutic options, AA remains a condition with significant unmet medical needs. The exact mechanisms driving the disease are not fully understood, and no universally effective treatment exists. Further research is essential to better understand the pathogenesis of AA and develop more effective and targeted therapies. This review emphasizes the need for continued exploration of innovative treatment strategies and a deeper understanding of the disease's ethological factors to improve patients’ outcomes.